2017
DOI: 10.1371/journal.pone.0176575
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide gene expression array identifies novel genes related to disease severity and excessive daytime sleepiness in patients with obstructive sleep apnea

Abstract: We aimed to identify novel molecular associations between chronic intermittent hypoxia with re-oxygenation and adverse consequences in obstructive sleep apnea (OSA). We analyzed gene expression profiles of peripheral blood mononuclear cells from 48 patients with sleep-disordered breathing stratified into four groups: primary snoring (PS), moderate to severe OSA (MSO), very severe OSA (VSO), and very severe OSA patients on long-term continuous positive airway pressure treatment (VSOC). Comparisons of the microa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Chen et al ( 27 ) observed that alteration of the natriuretic peptide receptor 2 and its pathways was associated with the clinical phenotype of daytime sleepiness in OSA patients. In a different study from Chen et al ( 34 ), decreased expression of BIRC3 gene was associated with the development of hypertension in OSA patients. In a relatively large sample ( N = 972) of the Cleveland Family Study, Patel et al ( 30 ) showed that insertion (I)/deletion (D) polymorphisms of the angiotensin converting enzyme were associated with hypertension in OSA patients with AHI > 30.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Chen et al ( 27 ) observed that alteration of the natriuretic peptide receptor 2 and its pathways was associated with the clinical phenotype of daytime sleepiness in OSA patients. In a different study from Chen et al ( 34 ), decreased expression of BIRC3 gene was associated with the development of hypertension in OSA patients. In a relatively large sample ( N = 972) of the Cleveland Family Study, Patel et al ( 30 ) showed that insertion (I)/deletion (D) polymorphisms of the angiotensin converting enzyme were associated with hypertension in OSA patients with AHI > 30.…”
Section: Resultsmentioning
confidence: 90%
“…The four studies reviewed, evaluated the genetic and epigenetic markers associated with OSA clinical phenotypes and hypertension ( 27 , 30 , 34 ). Chen et al ( 27 ) observed that alteration of the natriuretic peptide receptor 2 and its pathways was associated with the clinical phenotype of daytime sleepiness in OSA patients.…”
Section: Resultsmentioning
confidence: 99%
“…Another key gene was the angiomotin (AMOT), which plays an important part in angiogenesis [ 72 ]. More importantly, an OSAHS genome-wide gene expression array study showed that AMOT was involved in OSAHS-related excessive daytime sleepiness by regulating a variety of endothelial cell functions [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Wu et al 27 identified, after genotype analysis of data generated from dogs conditioned to high altitude, five genes related to hypoxia-adaptation signatures on the X chromosome, among which was the AMOT gene. At the clinical stage, an increase of AMOT p130 expression has been reported in a group of patients suffering from obstructive sleep apnoea 28 , confirming the implication of AMOT in chronic intermittent hypoxia with re-oxygenation. Overexpression of p80 and p130 isoforms in this context of revascularisation confirms previous data describing the expression profile of each isoform over the different steps of angiogenesis 29 .…”
Section: Discussionmentioning
confidence: 56%